Spermiogram and testicular morphological studies of the buck after treatment with ethanol leaf extract of spondias mombin (2017)
Twelve sexually matured West African Dwarf bucks from were used for the experiment. Plant extraction was by cold extraction method using hexane and ethanol as solvents. All the goats had bilaterally well descended free testicles. They were kept in standard goat pen, were served water ad libitum, centrosema plant and ration. They were stabilised for two weeks after which pre-treatment spermiogram was done followed by 14 days of oral administration of 800mg/kg ethanol leaf extract of Spondias mombin. Spermiogram was repeated after treatment. Two randomly selected goats were then castrated through a midline pre-scrotal incision for morphological study and histology of the testes and epididymides. Total spermatozoa morphological abnormalities in pre-treatment of 17.1% was significantly (p≤0.05) higher than the 10% recorded for post-treatment. Curved mid-piece (1.8%) and bent tail (1.8%) constituted the highest abnormalities post-treatment while curved tail (3.5%) was highest pre-treatment. Mean values of progressive motility and percentage liveability were significantly higher (p≤0.05) in post- treatment (96.17±3.10% and 98.25±1.36% respectively) compared to pre-treatment (80.83±11.84% and 78.75±9.56% respectively). Post-treatment sperm concentration (2.50±0.32 x109 cells/ml) compared with pre-treatment (2.32±0.36 x109 cells/ml) was not significantly different. Post-treatment gross and histological features of the bucks’ testes and epididymis were normal. The work revealed that Spondias mombin at 800mg/kgBW improved semen quality in bucks indicating its usefulness as a potential profertility agent.